Epidemiological Study of Two Wheeler Accident Victims In Rural South India - Reddy, Ananda; Balaraman , R (Journal of Indian Academy of Forensic Medicine, 2016)
Vehicular accidents are steadily mounting up on the Indian roads, so critical analysis of causative factors is pivotal to prevent them in future. This study was designed to assess the epidemiological factors constrained in two wheeler accident victims. It’s a cross-sectional study of two wheeler related deaths autopsied at the IGGGH & PGI in Pudducherry. Data gathered by interviews, autopsy and results were analysed. Two wheeler crashes were accountable for 10.85% of all 1318autopsies. Most vulnerable are males (81%) and individuals between 16-29 years (35%). Most victims were from rural area (47%), Hindus (79%), married (49%) and middle income (62%) group. These fatal events frequent on national highways (36%), evening rush traffic hours (42%) and involves motorcycle occupants (64%) and pedestrians (24%). Prime RTA contributors like human errors; vehicle and road factors were evaluated. Importing awareness and education among vulnerable population alleviate the frequency of accidents and dreaded outcomes.